Five-lump kinetic approach on biofuel production from refined rubber seed oil over Cu/ZSM-5 catalyst via catalytic cracking reaction. (June 2021) - Gurdeep Singh, Haswin Kaur; Yusup, Suzana; Quitain, Armando T.; Abdullah, Bawadi; Inayat, Abrar; Ameen, Mariam; Cheah, Kin Wai; Sasaki, Mitsuru; Kida, Tetsuya; Chai, Yee Ho
Abstract: The heavy utilization of fossil fuels and efforts to reduce carbon footprint worldwide led to the development of biofuels. Therefore, this paper investigates the kinetic study for the catalytic cracking reaction of refined rubber seed oil (RSO) for bio gasoline production using Cu/ZSM5 catalyst. The reaction was carried out at 440 ᵒ C and at atmospheric condition within the WHSV range of 1.5–3.5 h −1 in a fixed bed reactor. The kinetic rate constants were estimated based on 3, 4 and 5 lumped models sequentially. In the 3-lump model, the RSO was converted mostly to organic liquid product (OLP) and only forming some undesired gas and coke. Both refined RSO and OLP contributed to the formation of gas and coke products in the 4-lump model. In the 5-lump model, the RSO and OLP both favoured gasoline production. The absence of gaseous product suggests that no secondary cracking reactions occurred in gasoline fractions, but coke deposition was formed due to condensation. The high R 2 squared values suggest that the predicted model data was in good agreement with the experimental data. Highlights: Study of biogasoline conversion from refined RSO via five-lump kinetic approach was proposed. Lumped kinetic study of RSO conversion to biogasoline was compared against other literature. The catalytic cracking reaction using Cu/ZSM-5 catalyst obeyed first order kinetics. The kinetic rate constants for biogasoline and green diesel were determined.